2009
DOI: 10.1038/sj.bjc.6604885
|View full text |Cite
|
Sign up to set email alerts
|

Association of ERBB2 gene status with histopathological parameters and disease-specific survival in gastric carcinoma patients

Abstract: The clinical significance of ERBB2 amplification/overexpression in gastric cancer remains unclear. In this study, we evaluated the ERBB2 status in 463 gastric carcinomas using immunohistochemistry (IHC) and fluorescence in situ hybridisation (FISH), and compared the findings with histopathological characteristics and with disease-specific survival. ERBB2 overexpression (2 þ and 3 þ ) and amplification (ratio ERBB2/CEP17X2) were found in 43 (9.3%) and 38 (8.2%) gastric carcinomas, respectively. Perfect IHC/FISH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 41 publications
11
100
2
5
Order By: Relevance
“…Regarding anatomical location similar finding have been reported, with no difference between proximal and distal tumor, as we have found in our study (3,9,10,14,18,21) . Most studies conducted in Asia have also reported reactivity rates of 11.7% to 15.74%, similar to our findings, as well as the predominance of HER2 expression in the intestinal subtype (11,16,17,22) .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding anatomical location similar finding have been reported, with no difference between proximal and distal tumor, as we have found in our study (3,9,10,14,18,21) . Most studies conducted in Asia have also reported reactivity rates of 11.7% to 15.74%, similar to our findings, as well as the predominance of HER2 expression in the intestinal subtype (11,16,17,22) .…”
Section: Discussionsupporting
confidence: 92%
“…Among patients with AGC, the rate of human epidermal growth factor receptor 2 (HER2) positivity reportedly ranges from 8.2 to 23.0% as assessed by immunohistochemistry (IHC), and from 7.1 to 27.1% when assessed by fluorescence in situ hybridization (FISH) (12)(13)(14)(15). On the basis of the Trastuzumab for Gastric Cancer (ToGA) trial results, addition of trastuzumab to platinum-based chemotherapy has become the standard first-line therapy for HER2-positive AGC (16).…”
Section: Correlation Between Human Epidermal Growth Factor Receptor 2mentioning
confidence: 99%
“…Not specified Wang et al, 10 Im et al 27 [2 Studies] Marx et al, 15 Yu et al, 19 Hayashi et al, 22 Satiroglu-Tufan et al, 25 Ghaderi et al, 36 Allgayer et al 39 15 Barros-Silva et al, 16 Hayashi et al, 22 Park et al, 24 Tanner et al, 26 Song et al, 30 Garcia et al, 31 Lee et al, 32 Pintode-Sousa et al, 34 Oshima et al 38 [12 Studies (2 studies between 1990 and 1999 not displayed)]…”
Section: Presence Of Metastases (M)mentioning
confidence: 99%
“…III/IV Wang et al, 10 Zhang et al, 18 Im et al, 27 Ghaderi et al, 36 Allgayer et al 39 [5 Studies] Presence of microvascular invasion Wang et al, 10 Pinto-de-Sousa et al, 34 Allgayer et al 39 [3 Studies] Grabsch et al, 11 Barros-Silva et al, 16 Park et al, 24 Garcia et al 31 [8 Studies (4 studies between 1990 and 1999 not displayed)]…”
Section: Presence Of Metastases (M)mentioning
confidence: 99%